Relationship of Language Development with Society Development (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the relationship between language development and the development of society, the fact that language is a social phenomenon, its role and importance in the development and development of society are explained based on analytical thoughts.